The use of physiotherapy methods such as iontophoresis and phontophoresis in the treatment of scars - Aleksandra Gałuszka (Kazimierz Wielki University, 2022)
Scars are perceived as marring the body. Sometimes having a scar increases the feeling of shame and difference. There are people who are ashamed of their scars so much that they do not go to the swimming pool, gym or other places where it is necessary to expose the scar. In summer or on warm days, they cover their body to hide the scar. Sometimes, however, people consider having a scar as normal and function as they did before a scar was formed. The situational context of the scar formation is of particular importance, eg a traumatic event, a traffic accident, etc. Then, having a scar may cause psychological consequences in a person and then it is worth seeking help from a psychologist to reconcile with having a scar. Physiotherapy and cosmetology help people with unacceptable or functional disorders. Thanks to the use of many methods in these areas, it is possible to obtain partial removal of scars or their complete elimination, possibly minimizing the visibility of the lesion.